Product Market Competition and Convertible Debt Financing - Lei, Cheng; Lyandres, Evgeny; Veld, Chris; Xia, Ying (The Review of Corporate Finance Studies, 2026)
Competitive threats motivate firms to use convertible debt because the possibility of future conversion enhances financial flexibility. Consistent with this intuition, we find that the intensity of competitive threats is positively associated with convertible debt financing at both the extensive and intensive margins. By using large tariff reductions as exogenous shocks to competition we show that this relation is likely causal. Convertible debt usage in response to competitive threats strongly depends on a firm’s relative financial and competitive conditions. In addition, firms increase the probability of future conversion by tailoring convertible debt features. (JEL D34, G30, G32, G39)